Evaluation of Body Weight, Serum Lipid Profile, Glucose Homeostasis, Oxidative Stress and Hepatic Function in Healthy Mice Fed With Zinc Sulphate Supplementation (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The present research study was designed to evaluate the effect of zinc supplementation on body weight, serum triglyceride, cholesterol, glucose homeostasis, oxidative stress, and hepatic function in mice. Mice were treated with zinc sulphate at an equivalent weight of 6.5 mg/kg-body weight elemental zinc for four weeks. Bodyweight, serum glucose, triglyceride, cholesterol, serum MDA, nitric oxide, vitamin C, and hepatic enzymes level were determined at the end of the study period. Data from this study showed that supplementation with zinc in mice maintained a balanced blood glucose homeostasis throughout the experimental period. Moreover, treatment with zinc showed a significant (p